On the generation of enhanced lookup tables for wheel-rail contact models - Marques, Filipe (2019)
In railway dynamics, the interpolation of lookup tables (LUTs) is a procedure utilized to reduce the computational effort when computing the wheel-rail contact forces. However, the generation of LUTs with multiple inputs and multiple outputs is a challenging task for which aspects such as their minimal size and uniform accuracy over the LUT domain have not been systematically addressed in the literature. Thus, this work presents a comprehensive methodology for a detailed analysis of general LUTs, and identifies ways to improve them. For that, an analysis of the variation of the input parameters is made and the interpolation error is assessed on the cells and edges of the original table, then, based on this analysis, two enhanced LUTs are proposed. The first one is approximately 5 times smaller than the original but holds similar accuracy. The second table exhibits half of the maximum interpolation error of the original LUT but holds an identical size. The methodology is demonstrated here using the recently published Kalker Book of Tables for Non-Hertzian contact (KBTNH) but it can be used by any other LUT approach in order to improve accuracy and/or to reduce size.